Product Development in Islamic Financial Institutions (IFIS): An Extensive Literature Review - Al Adawiyah, Rumaisah Azizah; Ismail, Shafinar (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2025)
This paper aims to critically review existing studies related to IFIs products and their instruments, IFIs’ product development, and the agenda for IFIs’ product development in the future. This study is built upon an extensive literature review of the existing literature on IFIs, revisiting its objectives, its criticism, and looking at the Product Development Process of IFIs from previous studies. Considering IFIs product development, so far the process on IFIs lies on the need to be competitive thus imitating their conventional counterparts. However on the other side, there’s a need for developing the instruments without denying the fulfilment of Islamic law (maqasid al sharia) within the process. On the other hand, there are some arguments on to what extent Sharia principles or maqasid al sharia is being fulfilled as so far, the feasible indicators are still limited. As product development in IFIs is complex and demands innovations in many aspects, collaboration among global and Islamic Economy actors is needed. This paper implies that there’s a need for a comprehensive approach in formulating an ideal product development process for IFIs and giving urges to global Islamic Economy actors to collaborate.